Preparation method of Raney nickel catalyst for hydrogenation of 2-methylglutaronitrile
By modifying the Rainey nickel catalyst doped with metal elements, the problem of low selectivity in the 2-methylglutarnitrile hydrogenation reaction is solved, and higher reaction selectivity and conversion rate are achieved, and the stability of the catalyst is maintained.
Patent Information
- Application Number
- CN202411938821.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-25
AI Technical Summary
The Rainey nickel catalyst has a low selectivity for the target product 2-methylpentanediine in the 2-methylglutarnitrile hydrogenation reaction and produces a large number of unavailable heavy products at high reaction temperatures and pressures.
By using the nickel-aluminum alloy doped with metal elements as a support, using alkali etching and titanium-containing aqueous solution to support modification, a Rainie nickel catalyst with uniform distribution of a large number of active sites on the surface was prepared.
The selectivity and conversion rate of the 2-methylglutaritrile hydrogenation reaction are improved, and the stability of the catalyst remains unchanged after repeated use, maintaining high catalytic activity.
Smart Images

Figure BDA0005212126580000081 
Figure BDA0005212126580000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a method for preparing a Raney nickel catalyst for hydrogenating 2-methylglutaronitrile. Background Art
[0002] Raney nickel catalyst was first reported in 1925 and has become a common industrial catalyst in chemical production. Raney nickel catalyst is usually prepared by leaching nickel-aluminum alloy with alkali solution to dissolve the Al phase, and has a spongy, porous skeleton structure. With its low preparation cost and high catalytic activity, it is often used for catalytic hydrogenation of unsaturated hydrocarbons, carbonyl, nitrile, nitro, etc. At present, the main problem of Raney nickel catalyst in the hydrogenation reaction of 2-methylglutaronitrile is the low selectivity for the target product 2-methylpentanediamine. At higher reaction temperatures and pressures, more unusable heavy products will also be produced.
[0003] At present, there are few relevant literature reports on the catalytic hydrogenation of 2-methylglutaronitrile, which are mostly focused on the reaction process, and the preparation method of the catalyst used is rarely described. Patent CN111644196 discloses a highly selective preparation method of methylpentanediamine using a composite catalyst system. The composite catalyst system includes a modified supported Ni / Co main catalyst and a doped silicon-aluminum-based molecular sieve second catalyst as a co-catalyst system. Although the selectivity of the target product 2-methylpentanediamine is not less than 80%, the composite catalyst is complicated to prepare and difficult to mass produce. Rare earth metals are also doped, which is costly. Patent CN101990532 discloses a preparation method of methylpentanediamine and methylpiperidine. The catalyst used in the method is based on Raney cobalt doped with nickel and chromium, and the selectivity of the product 2-methylpentanediamine does not exceed 80%. At the same time, the preparation method of the catalyst is not described, and the stability of the catalyst is not investigated.
[0004] In summary, in order to further expand the application of Raney nickel catalytic system in the hydrogenation of 2-methylglutaronitrile, the Raney nickel catalyst was modified and doped, in order to obtain a simple and mass-producible preparation method, while improving the yield of 2-methylpentanediamine. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for preparing a Raney nickel catalyst for hydrogenation of 2-methylglutaronitrile. The Raney nickel doped with metal elements is used as a carrier, and a titanium source aqueous solution is introduced for loading. A large number of active sites can be evenly distributed on the surface of the obtained Raney nickel catalyst, and the metal synergistic effect is better. The catalyst is used for the hydrogenation reaction of 2-methylglutaronitrile to obtain higher reaction selectivity and conversion rate. Moreover, the catalyst remains stable after being used for 5 times and still has high catalytic activity.
[0006] The purpose of the present invention is achieved through the following technical solutions: The present invention provides a method for preparing a Raney nickel catalyst for hydrogenation of 2-methylglutaronitrile, comprising the following steps: (1) crushing the raw alloy NiAlX into powder; X is one or more of Mo, Fe, and Cr; (2) adding the alloy powder to an alkaline solution, stirring and ultrasonically treating the alloy powder, then heating and leaching the alloy powder, filtering the alloy powder, and obtaining a solid; (3) adding the solid into a titanium source aqueous solution for soaking treatment, filtering, and obtaining a Raney nickel catalyst.
[0007] The present invention uses a nickel-aluminum alloy doped with metal X as a carrier, first uses an alkali solution to etch the carrier to remove part of Al, and then immerses the carrier in a titanium source aqueous solution for titanium ion loading, so that a large number of active sites can be evenly distributed on the surface of the obtained Raney nickel catalyst. In addition, the metal elements contained in the Raney nickel catalyst cooperate to have higher reaction selectivity and conversion rate in the 2-methylglutaronitrile hydrogenation reaction, and in addition, through the coordinated control of the ratio of the raw material alloy, the treatment conditions of the alkali solution, and the concentration of the titanium source aqueous solution, the metal ratio in the obtained Raney nickel catalyst is more suitable for the 2-methylglutaronitrile hydrogenation reaction, and has a better catalytic effect while having higher structural stability, and the catalytic activity remains unchanged after repeated use for 5 times.
[0008] Preferably, in step (1), the raw material alloy NiAlX has a Ni content of 40-60wt%, an Al content of 35-55wt%, and the balance is X. More preferably, the raw material alloy NiAlX has a Ni content of 49-50wt%, an Al content of 48-49wt%, and the balance is X.
[0009] Preferably, in step (1), the particle size of the powder is 40-120 mesh, more preferably, the particle size is 60-100 mesh.
[0010] Preferably, in step (2), the concentration of the alkali solution is 15-30wt%, more preferably, the concentration is 20-30wt%; the alkali solution is a strong alkali solution, more preferably a sodium hydroxide solution and / or a potassium hydroxide solution.
[0011] Preferably, in step (2), the ultrasonic treatment time is 10-60 min, more preferably, the time is 10-30 min; the heating leaching temperature is 25-85°C, stirring is performed simultaneously, and the leaching time is 30-100 min; more preferably, the heating leaching temperature is 50-85°C, stirring is performed simultaneously, and the leaching time is 60-100 min.
[0012] Preferably, in step (3), the concentration of the titanium source-containing aqueous solution is 0.1-10 wt %, more preferably, the concentration is 3-6 wt %.
[0013] Preferably, in step (3), the titanium source includes one or more of sodium metatitanate, potassium titanate and titanium trichloride.
[0014] Preferably, in step (3), the soaking treatment is performed at 50-90°C for 3-10 hours, and more preferably, the soaking treatment is performed at 70-90°C for 4-8 hours.
[0015] Preferably, in step (3), after the soaking treatment is completed, a solid is obtained by filtration, and the solid is washed with deionized water and anhydrous ethanol to obtain a Raney nickel catalyst, and the obtained catalyst is stored in anhydrous ethanol for standby use.
[0016] Preferably, the total content of Ni and Al in the Raney nickel catalyst is 93-97.6wt%, the content of Ti is 0.1-5wt%, and the balance is X. More preferably, the total content of Ni and Al in the Raney nickel catalyst is 93-97.6wt%, the content of Ti is 1-5wt%, and the balance is X.
[0017] Compared with the prior art, the present invention has the following beneficial effects: the present invention uses Raney nickel doped with a metal element X as a carrier, introduces a titanium source-containing aqueous solution for loading modification, and obtains a Raney nickel catalyst having a large number of active sites uniformly distributed on the surface thereof, which is used for the hydrogenation reaction of 2-methylglutaronitrile, and can obtain a higher selectivity of the target product 2-methylpentanediamine, and the stability of the catalyst remains unchanged after being used 5 times. DETAILED DESCRIPTION
[0018] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto: The preparation of the Raney nickel catalyst for hydrogenation of 2-methylglutaronitrile in the present invention comprises the following steps: (1) crushing the raw alloy NiAlX (X is one or more of Mo, Fe, Cr) into powder with a powder particle size of 40-120 mesh; (2) adding the alloy powder to an alkali solution with a concentration of 15-30 wt%, stirring and ultrasonically treating for 10-60 min, then heating and leaching at a temperature of 25-85° C. for 30-100 min while stirring, filtering, and obtaining a solid; (3) adding the solid into a titanium source aqueous solution with a concentration of 0.1-10 wt % and soaking it at 50-90° C. for 3-10 h; after the soaking treatment is completed, filtering to obtain a solid, washing the solid with deionized water and anhydrous ethanol to obtain a Raney nickel catalyst, and storing the obtained catalyst in anhydrous ethanol for standby use.
[0019] In a specific embodiment of the present invention, in step (1), in the raw material alloy NiAlX, the Ni content is 40-60wt%, the Al content is 35-55wt%, and the balance is X.
[0020] In a specific embodiment of the present invention, in step (2), the alkali solution is a strong alkali solution, which can be a sodium hydroxide solution and / or a potassium hydroxide solution.
[0021] In a specific embodiment of the present invention, in step (3), the titanium source includes one or more of sodium metatitanate, potassium titanate and titanium trichloride.
[0022] In a specific embodiment of the present invention, the total content of Ni and Al in the obtained Raney nickel catalyst is 93-97.6wt%, the content of Ti is 0.1-5wt%, and the balance is X.
[0023] Example 1 The preparation of Raney nickel catalyst comprises the following steps: (1) grinding a raw material alloy NiAlCr (Ni content is 49.5wt%, Al content is 49wt%, Cr content is 1.5wt%) into powder with a powder particle size of 60-80 mesh; (2) adding the alloy powder to a 25 wt % NaOH solution, stirring and ultrasonically treating for 30 min, then stirring and leaching at 70° C. for 80 min, filtering, and washing with deionized water to obtain a solid; (3) The solid was added to a 5 wt% sodium metatitanate aqueous solution, immersed at 80°C for 6 h, filtered, and the obtained solid was washed with deionized water and anhydrous ethanol in turn to obtain a Raney nickel catalyst (the total content of Ni and Al was 94.4 wt%, the content of Ti was 2.8 wt%, and the content of Cr was 2.8 wt%), and finally stored in anhydrous ethanol for later use.
[0024] Example 2 The difference from Example 1 is that the raw material alloy is NiAlFe.
[0025] The preparation of Raney nickel catalyst comprises the following steps: (1) grinding a raw material alloy NiAlFe (Ni content is 49.5wt%, Al content is 49wt%, Fe content is 1.5wt%) into powder with a powder particle size of 60-80 mesh; (2) adding the alloy powder to a 25 wt % NaOH solution, stirring and ultrasonically treating for 30 min, then stirring and leaching at 70° C. for 80 min, filtering, and washing with deionized water to obtain a solid; (3) The solid was added to a 5 wt% sodium metatitanate aqueous solution, immersed at 80°C for 6 h, filtered, and the obtained solid was washed with deionized water and anhydrous ethanol in turn to obtain a Raney nickel catalyst (the total content of Ni and Al was 94.4 wt%, the content of Ti was 2.8 wt%, and the content of Fe was 2.8 wt%), and finally stored in anhydrous ethanol for later use.
[0026] Example 3 The difference from Example 1 is that the raw material alloy is NiAlMo.
[0027] The preparation of Raney nickel catalyst comprises the following steps: (1) grinding a raw material alloy NiAlMo (Ni content is 49.5wt%, Al content is 49wt%, Mo content is 1.5wt%) into powder with a powder particle size of 60-80 mesh; (2) adding the alloy powder to a 25 wt % NaOH solution, stirring and ultrasonically treating for 30 min, then stirring and leaching at 70° C. for 80 min, filtering, and washing with deionized water to obtain a solid; (3) The solid was added to a 5 wt% sodium metatitanate aqueous solution, immersed at 80°C for 6 h, filtered, and the obtained solid was washed with deionized water and anhydrous ethanol in turn to obtain a Raney nickel catalyst (the total content of Ni and Al was 94.4 wt%, the content of Ti was 2.8 wt%, and the content of Mo was 2.8 wt%), and finally stored in anhydrous ethanol for later use.
[0028] Example 4 The difference from Example 1 is that the raw material alloy NiAlCr has a Ni content of 49 wt %, an Al content of 49 wt %, and a Cr content of 2 wt %.
[0029] The preparation of Raney nickel catalyst comprises the following steps: (1) crushing the raw material alloy NiAlCr (Ni content is 49wt%, Al content is 49wt%, Cr content is 2wt%) into powder with a powder particle size of 60-80 mesh; (2) adding the alloy powder to a 25 wt % NaOH solution, stirring and ultrasonically treating for 30 min, then stirring and leaching at 70° C. for 80 min, filtering, and washing with deionized water to obtain a solid; (3) The solid was added to a 5 wt% sodium metatitanate aqueous solution, immersed at 80°C for 6 h, filtered, and the obtained solid was washed with deionized water and anhydrous ethanol in turn to obtain a Raney nickel catalyst (the total content of Ni and Al was 93.4 wt%, the content of Ti was 2.8 wt%, and the content of Cr was 3.8 wt%), and finally stored in anhydrous ethanol for later use.
[0030] Example 5 The difference from Example 1 is that the raw material alloy NiAlCr has a Ni content of 49 wt%, an Al content of 48.5 wt%, a Cr content of 2.5 wt%, and the titanium source aqueous solution is a titanium trichloride aqueous solution.
[0031] The preparation of Raney nickel catalyst comprises the following steps: (1) grinding a raw material alloy NiAlCr (Ni content: 49 wt %, Al content: 48.5 wt %, Cr content: 2.5 wt %) into powder with a powder particle size of 60-80 mesh; (2) adding the alloy powder to a 25 wt % NaOH solution, stirring and ultrasonically treating for 30 min, then stirring and leaching at 70° C. for 80 min, filtering, and washing with deionized water to obtain a solid; (3) The solid was added to a 5 wt% titanium trichloride aqueous solution, immersed at 80°C for 6 h, filtered, and the obtained solid was washed with deionized water and anhydrous ethanol in turn to obtain a Raney nickel catalyst (the total content of Ni and Al was 93.4 wt%, the content of Ti was 1.9 wt%, and the content of Cr was 4.7 wt%), and finally stored in anhydrous ethanol for later use.
[0032] Example 6 The difference from Example 1 is that the raw material alloy NiAlCr has a Ni content of 51 wt %, an Al content of 46.5 wt %, a Cr content of 2.5 wt %, and the titanium source aqueous solution is a potassium titanate aqueous solution.
[0033] The preparation of Raney nickel catalyst comprises the following steps: (1) grinding a raw material alloy NiAlCr (Ni content: 51wt%, Al content: 46.5wt%, Cr content: 2.5wt%) into powder with a powder particle size of 60-80 mesh; (2) adding the alloy powder to a 25 wt % NaOH solution, stirring and ultrasonically treating for 30 min, then stirring and leaching at 70° C. for 80 min, filtering, and washing with deionized water to obtain a solid; (3) The solid was added to a 5 wt% potassium titanate aqueous solution, immersed at 80°C for 6 h, filtered, and the obtained solid was washed with deionized water and anhydrous ethanol in turn to obtain a Raney nickel catalyst (the total content of Ni and Al was 94.5 wt%, the content of Ti was 0.9 wt%, and the content of Cr was 4.6 wt%), and finally stored in anhydrous ethanol for later use.
[0034] Example 7 The difference from Example 1 is that the raw material alloy is NiAlCrMo.
[0035] The preparation of Raney nickel catalyst comprises the following steps: (1) grinding a raw alloy NiAlCrMo (Ni content: 49.5wt%, Al content: 49wt%, Cr content: 1wt%, Mo content: 0.5wt%) into powder with a powder particle size of 60-80 mesh; (2) adding the alloy powder to a 25 wt % NaOH solution, stirring and ultrasonically treating for 30 min, then stirring and leaching at 70° C. for 80 min, filtering, and washing with deionized water to obtain a solid; (3) The solid was added to a 5 wt% sodium metatitanate aqueous solution, immersed at 80°C for 6 h, filtered, and the obtained solid was washed with deionized water and anhydrous ethanol in turn to obtain a Raney nickel catalyst (the total content of Ni and Al was 94.4 wt%, the content of Ti was 2.8 wt%, the content of Cr was 1.9 wt%, and the content of Mo was 0.9 wt%), and finally stored in anhydrous ethanol for later use.
[0036] Example 8 The difference from Example 1 is that the raw material alloy is NiAlCrMo.
[0037] The preparation of Raney nickel catalyst comprises the following steps: (1) crushing the raw alloy NiAlCrMo (Ni content is 49wt%, Al content is 49wt%, Cr content is 1wt%, Mo content is 1wt%) into powder with a powder particle size of 60-80 mesh; (2) adding the alloy powder to a 25 wt % NaOH solution, stirring and ultrasonically treating for 30 min, then stirring and leaching at 70° C. for 80 min, filtering, and washing with deionized water to obtain a solid; (3) The solid was added to a 5 wt% sodium metatitanate aqueous solution, immersed at 80°C for 6 h, filtered, and the obtained solid was washed with deionized water and anhydrous ethanol in turn to obtain a Raney nickel catalyst (the total content of Ni and Al was 93.4 wt%, the content of Ti was 2.8 wt%, the content of Cr was 1.9 wt%, and the content of Mo was 1.9 wt%), and finally stored in anhydrous ethanol for later use.
[0038] Example 9 The difference from Example 1 is that the raw material alloy is NiAlCrFe.
[0039] The preparation of Raney nickel catalyst comprises the following steps: (1) crushing a raw alloy NiAlCrFe (Ni content is 49wt%, Al content is 49wt%, Cr content is 1wt%, Fe content is 1wt%) into powder with a powder particle size of 60-80 mesh; (2) adding the alloy powder to a 25 wt % NaOH solution, stirring and ultrasonically treating for 30 min, then stirring and leaching at 70° C. for 80 min, filtering, and washing with deionized water to obtain a solid; (3) The solid was added to a 5 wt% sodium metatitanate aqueous solution, immersed at 80°C for 6 h, filtered, and the obtained solid was washed with deionized water and anhydrous ethanol in turn to obtain a Raney nickel catalyst (the total content of Ni and Al was 93.4 wt%, the content of Ti was 2.8 wt%, the content of Cr was 1.9 wt%, and the content of Fe was 1.9 wt%), and finally stored in anhydrous ethanol for later use.
[0040] Example 10 The difference from Example 1 lies in the concentration of the NaOH solution and the treatment conditions in step (2).
[0041] The preparation of Raney nickel catalyst comprises the following steps: (1) grinding a raw material alloy NiAlCr (Ni content is 49.5wt%, Al content is 49wt%, Cr content is 1.5wt%) into powder with a powder particle size of 60-80 mesh; (2) adding the alloy powder to a 30 wt % NaOH solution, stirring and ultrasonically treating for 30 min, then stirring and leaching at 80° C. for 90 min, filtering, and washing with deionized water to obtain a solid; (3) The solid was added to a 5 wt% sodium metatitanate aqueous solution, immersed at 80°C for 6 h, filtered, and the obtained solid was washed with deionized water and anhydrous ethanol in turn to obtain a Raney nickel catalyst (the total content of Ni and Al was 94.3 wt%, the content of Ti was 2.8 wt%, and the content of Cr was 2.9 wt%), and finally stored in anhydrous ethanol for later use.
[0042] Embodiment 11 The difference from Example 1 is that the concentration of the sodium metatitanate aqueous solution is 3 wt %.
[0043] The preparation of Raney nickel catalyst comprises the following steps: (1) grinding a raw material alloy NiAlCr (Ni content is 49.5wt%, Al content is 49wt%, Cr content is 1.5wt%) into powder with a powder particle size of 60-80 mesh; (2) adding the alloy powder to a 25 wt % NaOH solution, stirring and ultrasonically treating for 30 min, then stirring and leaching at 70° C. for 80 min, filtering, and washing with deionized water to obtain a solid; (3) The solid was added to a 3 wt % sodium metatitanate aqueous solution, immersed at 80° C. for 6 h, filtered, and the obtained solid was washed with deionized water and anhydrous ethanol in turn to obtain a Raney nickel catalyst (the total content of Ni and Al was 95.5 wt %, the content of Ti was 1.7 wt %, and the content of Cr was 2.8 wt %), and finally stored in anhydrous ethanol for later use.
[0044] Example 12 The difference from Example 1 is that the concentration of the sodium metatitanate aqueous solution is 7 wt %.
[0045] The preparation of Raney nickel catalyst comprises the following steps: (1) grinding a raw material alloy NiAlCr (Ni content is 49.5wt%, Al content is 49wt%, Cr content is 1.5wt%) into powder with a powder particle size of 60-80 mesh; (2) adding the alloy powder to a 25 wt % NaOH solution, stirring and ultrasonically treating for 30 min, then stirring and leaching at 70° C. for 80 min, filtering, and washing with deionized water to obtain a solid; (3) The solid was added to a 7 wt % sodium metatitanate aqueous solution, immersed at 80° C. for 6 h, filtered, and the obtained solid was washed with deionized water and anhydrous ethanol in turn to obtain a Raney nickel catalyst (the total content of Ni and Al was 93.3 wt %, the content of Ti was 3.9 wt %, and the content of Cr was 2.8 wt %), and finally stored in anhydrous ethanol for later use.
[0046] Comparative Example 1 The difference from Example 1 is that no titanium source is loaded.
[0047] The preparation of Raney nickel catalyst comprises the following steps: (1) grinding a raw material alloy NiAlCr (Ni content is 49.5wt%, Al content is 49wt%, Cr content is 1.5wt%) into powder with a powder particle size of 60-80 mesh; (2) adding the alloy powder to a 25 wt % NaOH solution, stirring and ultrasonically treating for 30 min, then stirring and leaching at 70° C. for 80 min, filtering, and washing with deionized water to obtain a solid; (3) The solid was added into pure water, immersed at 80° C. for 6 h, filtered, and the obtained solid was washed with deionized water and anhydrous ethanol in turn to obtain a Raney nickel catalyst (the total content of Ni and Al was 97.1 wt %, and the content of Cr was 2.9 wt %), and finally stored in anhydrous ethanol for later use.
[0048] Comparative Example 2 The difference from Example 1 is that the concentration of the sodium metatitanate aqueous solution is 0.5 wt %.
[0049] The preparation of Raney nickel catalyst comprises the following steps: (1) grinding a raw material alloy NiAlCr (Ni content is 49.5wt%, Al content is 49wt%, Cr content is 1.5wt%) into powder with a powder particle size of 60-80 mesh; (2) adding the alloy powder to a 25 wt % NaOH solution, stirring and ultrasonically treating for 30 min, then stirring and leaching at 70° C. for 80 min, filtering, and washing with deionized water to obtain a solid; (3) The solid was added to a 0.5 wt% sodium metatitanate aqueous solution, immersed at 80°C for 6 h, filtered, and the obtained solid was washed with deionized water and anhydrous ethanol in turn to obtain a Raney nickel catalyst (the total content of Ni and Al was 96.8 wt%, the content of Ti was 0.3 wt%, and the content of Cr was 2.9 wt%), and finally stored in anhydrous ethanol for later use.
[0050] The catalytic activity of the Raney nickel catalysts of the examples and comparative examples was evaluated. The specific conditions were as follows: an ethanol solution containing 20 wt% of 2-methylglutaronitrile, a Raney nickel catalyst (10 wt% of 2-methylglutaronitrile), and aqueous ammonia (1 wt% of the total solution) were mixed and placed in an autoclave. The reaction was carried out at a hydrogen pressure of 6 MPa and a temperature of 80° C. until the hydrogen pressure in the autoclave remained unchanged for half an hour, the reaction was stopped, and the reaction product was analyzed.
[0051] The stability of the Raney nickel catalyst was tested. After each reaction, the catalyst was collected, washed with deionized water and anhydrous ethanol, and then reused.
[0052] 2-methylglutaronitrile conversion rate / %=(the amount of 2-methylglutaronitrile before the reaction−the amount of 2-methylglutaronitrile after the reaction) / the amount of 2-methylglutaronitrile before the reaction*100%.
[0053] 2-methylpentanediamine selectivity / %=the amount of substance of 2-methylpentanediamine / (the amount of substance of 2-methylglutaronitrile before the reaction−the amount of substance of 2-methylglutaronitrile after the reaction)*100%.
[0054] Table 1 Catalytic activity evaluation results of catalysts prepared in different embodiments As shown in Table 1, in the present invention, the present invention uses Raney nickel doped with metal element X as a carrier, introduces a titanium source aqueous solution for loading modification, and a large number of active sites are evenly distributed on the surface of the obtained Raney nickel catalyst, which is used for the hydrogenation reaction of 2-methylglutaronitrile, and can obtain a high 2-methylglutaronitrile conversion rate and a high target product 2-methylpentanediamine selectivity, and the catalytic stability of the catalyst after being reused 5 times remains unchanged, and still has a high conversion rate and selectivity. Among them, the raw material alloy when the metal element X is Cr is used as a carrier, and the Raney nickel catalyst obtained after loading the titanium source can have a higher catalytic activity, and it is applied to the hydrogenation reaction of 2-methylglutaronitrile, and a higher reaction selectivity can also be obtained, and a higher yield of the target product can be obtained.
[0055] Comparative Examples 1 and 2 show that the Raney nickel catalyst without titanium source loading or with too little titanium source loading exhibits low catalytic activity in the hydrogenation reaction of 2-methylglutaronitrile, and thus has low reaction conversion rate and selectivity, and the catalytic stability after repeated use is also poor.
[0056] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a Raney nickel catalyst for hydrogenation of 2-methylglutaronitrile, characterized in that: The steps include: (1) crushing the raw alloy NiAlX into powder; X is one or more of Mo, Fe, and Cr; (2) adding the alloy powder to an alkaline solution, stirring and ultrasonically treating the solution, then heating and leaching the solution, filtering the solution, and obtaining a solid; (3) The solid is added into a titanium source-containing aqueous solution for soaking and filtering to obtain a Raney nickel catalyst.
2. The method for preparing the Raney nickel catalyst for hydrogenation of 2-methylglutaronitrile according to claim 1, characterized in that: In step (1), in the raw alloy NiAlX, the Ni content is 40-60wt%, the Al content is 35-55wt%, and the balance is X.
3. The method for preparing the Raney nickel catalyst for hydrogenation of 2-methylglutaronitrile according to claim 1 or 2, characterized in that: In step (1), the particle size of the powder is 40-120 mesh.
4. The method for preparing the Raney nickel catalyst for hydrogenation of 2-methylglutaronitrile according to claim 1, characterized in that: In step (2), the concentration of the alkali solution is 15-30wt%; the alkali solution is a strong alkali solution.
5. The method for preparing the Raney nickel catalyst for hydrogenation of 2-methylglutaronitrile according to claim 1 or 4, characterized in that: In step (2), the ultrasonic treatment time is 10-60 minutes; the heating leaching temperature is 25-85°C, stirring is performed simultaneously, and the leaching time is 30-100 minutes.
6. The method for preparing the Raney nickel catalyst for hydrogenation of 2-methylglutaronitrile according to claim 1, characterized in that: In step (3), the concentration of the titanium source-containing aqueous solution is 0.1-10 wt %.
7. The method for preparing the Raney nickel catalyst for hydrogenation of 2-methylglutaronitrile according to claim 1, characterized in that: In step (3), the titanium source includes one or more of sodium metatitanate, potassium titanate and titanium trichloride.
8. The method for preparing the Raney nickel catalyst for hydrogenation of 2-methylglutaronitrile according to claim 1, 6 or 7, characterized in that: In step (3), the soaking treatment is performed at 50-90° C. for 3-10 hours.
9. The method for preparing the Raney nickel catalyst for hydrogenation of 2-methylglutaronitrile according to claim 1, 6 or 7, characterized in that: In step (3), after the soaking treatment is completed, a solid is obtained by filtration, and the solid is washed with deionized water and anhydrous ethanol to obtain a Raney nickel catalyst. The obtained catalyst is stored in anhydrous ethanol for standby use.
10. The method for preparing the Raney nickel catalyst for hydrogenation of 2-methylglutaronitrile according to claim 1, characterized in that: The total content of Ni and Al in the Raney nickel catalyst is 93-97.6wt%, the content of Ti is 0.1-5wt%, and the balance is X.
Citation Information
Cited By
Mo-Ni bimetallic denitration catalyst and preparation method thereof
CN121669252A